The "Hawthorne effect" - what did the original Hawthorne studies actually show? - Wickström, Gustav; Bendix, T (Scandinavian Journal of Work, Environment & Health, 2000)
The "Hawthorne effect" is often mentioned as a possible explanation for positive results in intervention studies. It is used to cover many phenomena, not only unwitting confounding of variables under study by the study itself, but also behavioral change due to an awareness of being observed, active compliance with the supposed wishes of researchers because of special attention received, or positive response to the stimulus being introduced. At times, the term seems to be used as a social equivalent to "placebo effect". In social research, there is much critical literature indicating that, in general, the term "Hawthorne effect" should be avoided. Instead of referring to the ambiguous and disputable Hawthorne effect when evaluating intervention effectiveness, researchers should introduce specific psychological and social variables that may have affected the outcome under study but were not monitored during the project, along with the possible effect on the observed results.
Keywords: context; evaluation; interpretation; intervention; paradigm; working life; worklife